The Competitive Diamond A proposal for the cluster of microenterprises in the clothing sector of the Pasa parish in Tungurahua - Lascano Aimacaña, Nelson (2019)
The purpose of this research work is to establish a proposal to enhance the growth and positioning of micro enterprises in the clothing sector of Pasa Parish in Tungurahua. The investigation has two phases: the one that analyzes the commercialization systems and the profitability; and the other phase oriented to establish the Competitive Diamond, by means of a Diagnosis of the productive chains and the establishment of competitive strategies for this sector. Through the development of the cluster model as a research proposal, the appropriate conditions for its development and business growth in this sector are stipulated. DOI: https://doi.org/10.31164/bcoyu.22.2019.721 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/721